The Influence of Influencer Marketing and Price Discount on Online Purchasing Decisions in the Shopee Marketplace - Desi Nurmala; Netti Nurlenawati; Dexi Triadinda (International Journal of Economics and Management Research, 2025)
Influencer marketing and price discounts are two marketing strategies that are most often used to drive consumer purchasing decisions in the digital era, especially on marketplace platforms such as Shopee. Influencer marketing refers to promotional efforts made by influential individuals to influence their audience, while price discounts are price cut strategies that provide added value directly to consumers. This study aims to analyze the influence of influencer marketing and price discounts on online purchasing decisions in the Shopee marketplace. The research method used is quantitative descriptive with a verification approach. Data were collected by distributing online questionnaires to 105 respondents selected using purposive sampling techniques. The data analysis technique used multiple linear regression with the help of SPSS version 26 software. The results of the study showed that influencer marketing and price discounts have a positive and significant effect on purchasing decisions, both partially and simultaneously. This finding confirms that a marketing strategy that combines collaboration with credible influencers and providing attractive price discounts can be an effective combination in increasing consumer purchasing decisions. The implication of this study is the importance for business actors in the marketplace to design adaptive and integrated marketing strategies in order to compete optimally amidst increasingly tight digital competition.